CFTR‐France, a national relational patient database for sharing genetic and phenotypic data associated with rare CFTR variants. Issue 10 (28th June 2017) - Claustres, Mireille; Thèze, Corinne; des Georges, Marie; Baux, David; Girodon, Emmanuelle; Bienvenu, Thierry; Audrezet, Marie‐Pierre; Dugueperoux, Ingrid; Férec, Claude; Lalau, Guy; Pagin, Adrien; Kitzis, Alain; et al.
Abstract : Based on 30 years' experience of CFTR testing, we have established a database intended to collect, curate, store and analyze rare CFTR variants from a network of experts that can significantly contribute associated data including detailed demographics, phenotype characteristics, cis/trans ‐allelic associations, relevant in silico or in vitro functional data and clinical or epidemiological observations that could be useful to consensually classify or re‐classify variants and genotype‐phenotype correlations. CFTR ‐France currently compiles 16, 819 variant records and 736 different variants from 4, 615 individuals. Abstract: Most of the 2, 000 variants identified in the CFTR (cystic fibrosis transmembrane regulator) gene are rare or private. Their interpretation is hampered by the lack of available data and resources, making patient care and genetic counseling challenging. We developed a patient‐based database dedicated to the annotations of rare CFTR variants in the context of their cis‐ and trans‐allelic combinations. Based on almost 30 years of experience of CFTR testing, CFTR ‐France (https://cftr.iurc.montp.inserm.fr/cftr ) currently compiles 16, 819 variant records from 4, 615 individuals with cystic fibrosis (CF) or CFTR‐RD (related disorders), fetuses with ultrasound bowel anomalies, newborns awaiting clinical diagnosis, and asymptomatic compound heterozygotes. For each of the 736 different variants reported in the database, patient characteristics and genetic information (other variations in cis or in trans) have been thoroughly checked by a dedicated curator. Combining updated clinical, epidemiological, in silico, or in vitro functional data helps to the interpretation of unclassified and the reassessment of misclassified variants. This comprehensive CFTR database is now an invaluable tool for diagnostic laboratories gathering information on rare variants, especially in the context of genetic counseling, prenatal and preimplantation genetic diagnosis. CFTR ‐France is thus highly complementary to the international database CFTR2 focused so far on the most common CF‐causing alleles.